2021
DOI: 10.3390/met11020327
|View full text |Cite
|
Sign up to set email alerts
|

Stress Corrosion Cracking Probability of Selective Laser Melted 316L Austenitic Stainless Steel under the Effect of Grinding Induced Residual Stresses

Abstract: Surface quality and dimensional tolerances of the selective laser melting (SLM) process are not good enough for many industrial applications and grinding as a common finishing process introduces many surface modifications. Investigation on the effect of grinding induced surface residual stress (RS) on early stages of stress corrosion cracking (SCC) of SLM manufactured 316L austenitic stainless steel was conducted. Potentiodynamic and galvanostatic tests in a 3.5% NaCl aqueous solution, XRD, SEM and energy-disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 63 publications
3
10
0
1
Order By: Relevance
“…Therefore, it can be stated that the enhanced localized corrosion resistance of L-PBF 718 specimens under tensile loading, which is the case in almost all industrial applications, could be attributed to submicron structure and higher integrity of passive layer compared to the conventional material. These findings are also in complete agreement with the authors' previous investigations on L-PBF 316 L austenitic stainless steels, identifying the impact of columnar subgrain width on localized corrosion susceptibility [51,52]. Moreover, in a recent study on SCC behaviour of L-PBF 316 L by Cruz et al [74], they indicated higher SCC resistance of L-PBF specimens compared to wrought counterparts as a result of significantly higher resistance of L-PBF specimens to pitting corrosion, leading to less possible active sites for crack initiation.…”
Section: Microstructural Effects On the Electrochemical Behaviour And...supporting
confidence: 92%
See 3 more Smart Citations
“…Therefore, it can be stated that the enhanced localized corrosion resistance of L-PBF 718 specimens under tensile loading, which is the case in almost all industrial applications, could be attributed to submicron structure and higher integrity of passive layer compared to the conventional material. These findings are also in complete agreement with the authors' previous investigations on L-PBF 316 L austenitic stainless steels, identifying the impact of columnar subgrain width on localized corrosion susceptibility [51,52]. Moreover, in a recent study on SCC behaviour of L-PBF 316 L by Cruz et al [74], they indicated higher SCC resistance of L-PBF specimens compared to wrought counterparts as a result of significantly higher resistance of L-PBF specimens to pitting corrosion, leading to less possible active sites for crack initiation.…”
Section: Microstructural Effects On the Electrochemical Behaviour And...supporting
confidence: 92%
“…6) for both L-PBF and conventional samples, while after tensile loading, conventional specimens exhibit lower E corr compared to L-PBF. Potentiodynamic results suggest a higher sensitivity of E break and breakdown current density (i break ) to tensile stress state than E corr and i corr highlighting a significant correlation between breakdown electrochemical parameters with the stress state of both groups, which is consistent with authors' previous investigations on 316 L austenitic stainless steel [50][51][52] using standard test methods, highlighting the similarity of potentiodynamic polarization behaviour between standard and microcapillary method, confirming the stability and high precision of the measurements in the current study. The potentiodynamic polarization results are summarized in Table 3.…”
Section: Electrochemical Responsesupporting
confidence: 90%
See 2 more Smart Citations
“…SCC is believed to be the most critical type of localized environmentally assisted damage, taking place owing to the synergistic effect of susceptible material, aggressive environment (unique to the material), and tensile stresses [9,10]. Stainless steels are widely considered susceptible to SCC in chloride-containing environments under applied or residual tensile stresses [11][12][13][14][15][16]. While international standards (AISI (UNS), ASTM) specify an acceptable range for the Cr content for each alloy designation (For instance, ASTM A276/A276M-17 allows a range between 18 and 20 wt% of Cr for AISI 304), the question that emerges is whether the permitted range could affect the corrosion characteristics and eventually higher SCC susceptibility for the lower limit.…”
Section: Introductionmentioning
confidence: 99%